Influence law on the effect of shredding characteristics of residual film in the mixture of mechanically recovered residual films and impurities in cotton fields - Liang, Rongqing; Wu, Guide; Jia, Ran; Meng, Hewei; Tai, Rongjian; Jia, Hepeng; Li, Fengkun; Za, Kan; Yaping, Li; Zhang, Bingcheng; et al. (International Journal of Agricultural and Biological Engineering, 2025)
Few studies have been carried out on special shredding technology and equipment, hence it is hard to find out the characteristic rule of distribution of residual films after shredding. By evaluating the mechanical properties of the residual film during the cutting process of a mixture of mechanically recovered residual film and impurities, the main parameters influencing the film distribution feature were acquired. Physical tests were conducted on the basis of a multi-blade toothed shredding device. A relationship model between the film distribution feature and main parameters was constructed through the central grouping method and regression analysis of variance, aiming to investigate the influence rule of main parameters on the film distribution feature and the interaction between them, and to obtain the optimal combination of parameters for the cutting device. The difference between the experimental validation value and the model prediction ranged from 1.03% to 9.56%, which showed that the model has reliable and accurate predictive ability. Keywords: mixture of residual film and impurities, residual film, multi-blade toothed cutters, shredding, distribution feature DOI: 10.25165/j.ijabe.20251801.8508 Citation: Liang R Q, Wu G D, Jia R, Meng H W, Tai R J, Jia H P, et al. Influence law on the effect of shredding characteristics of residual film in the mixture of mechanically recovered residual films and impurities in cotton fields. Int J Agric & Biol Eng, 2025; 18(1): 51–63.